Nonlinear Analysis for Investigating Seismic Performance of a Spun Pile-Column of Viaduct Structure - A. Fajar Setiawan; A. Kurniawan Santoso; M. Fauzi Darmawan; Agus Darmawan Adi; Sito Ismanti (Salehan Institute of Higher Education, 2023)
Slab-on-pile SOP viaducts have been constructed on several highways and railways in Indonesia, but there are certain doubts about some practical structural seismic design concepts. Therefore, this study aims to investigate the seismic performance of a single spun pile column for the SOP viaduct using nonlinear analysis. The essential variables used include the effect of top pile reinforced concrete infill treatment, soil-pile structure interaction (SPSI), and different response modification factors (R). Moreover, the single spun pile column was designed as a macro model with a force-based beam-column element having a fiber section in the plastic hinge. The static pushover analysis and quasi-static cyclic were also conducted to determine the displacement limit state and the equal viscous damping, respectively. Furthermore, seven pairs of ground motion excitations were used to investigate seismic performance in line with ASCE 7-10 and ASCE 61-14. The results showed that the implementation of the top-pile reinforced concrete infill treatment slightly reduced seismic response but evoked more severe pile curvature in the embedded zone. In addition, the behavior and seismic performance were slightly better than those without treatment when considering the SPSI. This study recommends the spun pile column for the SOP viaduct with a response modification factor of 1.5 to avoid probable brittle failure occurrence under earthquake load.Â Doi: 10.28991/CEJ-2023-09-07-02 Full Text: PDF